The influence of eco-friendly product labels on university students’ purchasing decisions - Husin, Nor Azilah; Al Yahyaei, Nasser; Min, Thain Lar Min; Bo, Wai Yan; Zakaria, Nurul Izzati; Lwin, Aye Myint Zu (Journal of Islamic, Social, Economics and Development, 2026)
Eco-friendly product labels have become an important marketing tool for encouraging sustainable consumer behavior. This study examines the influence of eco-friendly product labels on the purchasing decisions of 182 students at an International University, focusing on environmental concern, perceived value, and the visibility of eco-labels in advertisements. Data were collected through an online questionnaire and analyzed using SPSS. The findings revealed that perceived value was the strongest predictor of purchasing decisions, followed by the visibility of eco-labels in advertisements and environmental concerns. Although most respondents demonstrated moderate awareness of eco-labels, this awareness did not consistently translate into actual purchasing behavior. The study highlights the importance of emphasizing the value, credibility, and visibility of eco-labels to encourage sustainable consumption. These findings provide useful insights for marketers and policymakers while contributing to the understanding of green consumer behavior among university students.